G-c3n4 grain boundary modified garnet electrolyte ceramic and preparation and application thereof

CN123003281APending Publication Date: 2026-10-30TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611497631.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]然而,石榴石型固态电解质普遍存在离子电导率偏低、空气稳定性较差和不易烧结的问题,严重制约其规模化应用与产业化推广

Benefits of technology

(1)本发明通过在Li6.5La3Zr1.5(Ta0.5)O12的晶界添加g-C3N4进行改性,制备g-C3N4晶界改性石榴石型电解质陶瓷Li6.5La3Zr1.5(Ta0.5)O12-2~3wt%-g-C3N4。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003281A_ABST
    Figure CN123003281A_ABST
Patent Text Reader

Abstract

The application discloses g-C3N4 grain boundary modified garnet electrolyte ceramic and preparation and application thereof, belongs to the technical field of solid-state batteries, and has the chemical formula Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -2~3wt%-g-C3N4.The g-C3N4 grain boundary modified garnet electrolyte ceramic prepared by using the g-C3N4 grain boundary modified garnet electrolyte ceramic and the preparation and application thereof has high ion conductivity and excellent air stability, and can improve the cycle stability of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery technology, and in particular to g-C3N4 grain boundary modified garnet-type electrolyte ceramics and their preparation and application. Background Technology

[0002] Lithium-ion batteries are characterized by high energy density, long range, and long lifespan, and are currently widely used in various new energy vehicles and mobile communications. Most lithium batteries on the market are liquid lithium batteries. While liquid electrolytes have high ionic conductivity, they also have drawbacks such as easy decomposition at high temperatures, easy leakage, and the flammability and corrosiveness of leaked electrolytes, which can easily cause fires, explosions, and other accidents, posing safety hazards. With the widespread use of new energy vehicles, there is a demand for higher safety and longer range for lithium batteries. Solid-state batteries, with their good safety performance and high energy density, have become a research hotspot. The performance of the solid electrolyte is crucial to the performance of solid-state batteries. Garnet-type solid electrolytes, with their high energy density and wide electrochemical window, are considered one of the most promising solid electrolyte materials for promoting the commercialization of all-solid-state lithium metal batteries.

[0003] However, garnet-type solid electrolytes generally suffer from low ionic conductivity, poor air stability, and difficulty in sintering, which severely restricts their large-scale application and industrialization. Summary of the Invention

[0004] The purpose of this invention is to provide g-C3N4 grain boundary modified garnet-type electrolyte ceramics, their preparation and application. The prepared g-C3N4 grain boundary modified garnet-type electrolyte ceramics have high ionic conductivity and excellent air stability, which can improve the cycle stability of solid-state batteries.

[0005] To achieve the above objectives, this invention provides g-C3N4 grain boundary modified garnet-type electrolyte ceramics, the chemical formula of which is Li. 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -2~3wt%-g-C3N4.

[0006] Preferably, the g-C3N4 grain boundary modified garnet solid electrolyte has an ionic conductivity of 7.08 × 10⁻⁶. -4 ~7.21×10 -4 S / cm, relative density is 95%~97.9%.

[0007] The preparation of the above-mentioned g-C3N4 grain boundary modified garnet-type electrolyte ceramic includes the following steps: S1, according to Li 6.5La3Zr 1.5 (Ta 0.5 )O 12 The stoichiometric ratios of each element in the mixture were measured separately for lithium source, lanthanum source, zirconium source and tantalum source, and mixed to obtain a mixture. The mixture was then ground to obtain precursor powder. S2. Calcining melamine yields g-C3N4; S3. The precursor powder is calcined to obtain electrolyte powder. The electrolyte powder and g-C3N4 are used as ceramic mixture. The ceramic mixture is ball-milled and pressed into shape to obtain electrolyte green body. S4. The electrolyte blank is sintered, kept at a certain temperature and then cooled to obtain g-C3N4 grain boundary modified garnet type electrolyte ceramic.

[0008] Preferably, in S1, the lithium source is one or more of lithium carbonate and lithium hydroxide, the lanthanum source is lanthanum oxide, the zirconium source is one or more of zirconium oxide and zirconium oxynitrate, and the tantalum source is tantalum oxide.

[0009] Preferably, in S1, the grinding is carried out by wet ball milling, with a rotation speed of 400-500 r / min and a time of 8-15 h; The dispersant used in wet ball milling is one of isopropanol, ethanol, or methanol, and the milling beads used are zirconia balls. The mass ratio of the mixture, dispersant, and milling beads is 1:(1-2):(3-10).

[0010] Furthermore, in S1, according to Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 When weighing the corresponding raw materials according to the stoichiometric ratio of each element, the lithium source is in excess by 15 wt% to compensate for the volatilization of lithium at high temperature.

[0011] Preferably, in S2, the specific operation of calcination is as follows: under an air atmosphere, white melamine powder is placed in a muffle furnace and heated to the target temperature, then kept at that temperature, and then cooled to a furnace temperature ≤50℃. The heating rate is 3-6℃ / min, the target temperature is 550℃, the holding time is 3-4h, and the cooling rate is 1-3℃ / min.

[0012] Furthermore, in S2, the crucible used for calcination is a covered alumina crucible.

[0013] Preferably, in S3, the specific operation of calcination is as follows: under an air atmosphere, the precursor powder is placed in a muffle furnace and heated to the target temperature, then held at that temperature, and then cooled to a furnace temperature ≤50°C. The heating rate is 3-6℃ / min, the target temperature is 950-1100℃, the holding time is 4-8h, and the cooling rate is 1-3℃ / min.

[0014] Preferably, in S3, the ball milling is a wet ball milling process with a rotation speed of 400-500 r / min and a time of 8-15 h; The dispersant used in wet ball milling is one of isopropanol, ethanol, and methanol, and the milling beads are zirconia balls. The mass ratio of ceramic mixture, dispersant, and grinding beads is 1:(1-2):(3-10).

[0015] Furthermore, in S3, the crucible used for calcination is a covered magnesium oxide crucible.

[0016] Furthermore, after ball milling in S3, the resulting ball mill slurry is dried and then pressed into shape; the drying temperature is 60-80℃ and the time is 6-12h.

[0017] In S3, cold isostatic pressing is used for compression molding, with a pressure of 4-8 MPa, a temperature of 20-30℃, and a holding time of 2-5 minutes.

[0018] In S3, the pressing and molding process takes place in a mold, the inner diameter of which is determined according to the size of the button battery casing.

[0019] Preferably, in S4, sintering is carried out under a nitrogen or argon atmosphere, the sintering temperature is 1100-1200℃, the heating rate is 3-6℃ / min, and the holding time is 4-8h. Cool to 20-50℃ at a rate of 2-6℃ / min.

[0020] In S4, sintering is carried out in a tube furnace using a covered magnesium oxide crucible. During sintering, precursor powder can be spread evenly at the bottom of the magnesium oxide crucible to prevent the electrolyte preform from sticking to the crucible. Simultaneously, precursor powder can be applied to the surface of the electrolyte preform to prevent lithium volatilization due to high temperatures during sintering. During sintering, the g-C3N4 grain boundary-modified garnet solid electrolyte particles in the electrolyte preform grow and react chemically with the g-C3N4, resulting in ceramic densification and uniform shrinkage.

[0021] This invention also provides the application of g-C3N4 grain boundary modified garnet-type electrolyte ceramics in the preparation of solid-state batteries.

[0022] Furthermore, the solid-state battery is a lithium-ion solid-state battery.

[0023] Furthermore, the preparation method of lithium-ion solid-state batteries includes the following steps: The g-C3N4 grain boundary modified garnet-type electrolyte ceramic was successively polished, ultrasonically cleaned, and dried to serve as the electrolyte. A button cell, i.e., a lithium-ion solid-state battery, was assembled in an argon-filled glove box using lithium foil as the anode and lithium iron phosphate as the cathode.

[0024] Furthermore, ultrasonic cleaning was performed in ethanol for 30-60 seconds, with an ethanol concentration of 99.7%.

[0025] Therefore, the present invention, using the above-mentioned g-C3N4 grain boundary modified garnet-type electrolyte ceramic and its preparation and application, has the following beneficial effects: (1) This invention prepares g-C3N4 grain boundary modified garnet-type electrolyte ceramics Li6.5La3Zr1.5(Ta0.5)O12 by adding g-C3N4 to the grain boundaries of Li6.5La3Zr1.5(Ta0.5)O12 for modification. 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -2~3wt%-g-C3N4.

[0026] (2) The present invention utilizes Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 Before secondary ball milling, g-C3N4 powder was added to prepare g-C3N4 grain boundary modified garnet-type electrolyte ceramics. The addition of g-C3N4 powder can promote sintering, improve the grain boundary contact of solid electrolyte, and thus increase the density of garnet solid electrolyte. Secondly, the added g-C3N4 powder will also react chemically with lithium ions during sintering to generate lithium nitride. Both can accelerate the lithium ion transport rate and improve ionic conductivity and air stability.

[0027] (3) The g-C3N4 grain boundary modified garnet solid-state battery prepared by using g-C3N4 grain boundary modified garnet electrolyte ceramic in this invention can exhibit excellent cycle stability.

[0028] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0029] Figure 1 These are XRD patterns of garnet-type electrolyte ceramics modified with different amounts of g-C3N4 grain boundaries obtained in Examples 1-2 and Comparative Examples 1-3 of this invention. Figure 2 These are SEM images of garnet-type electrolyte ceramics modified with different amounts of g-C3N4 grain boundaries, prepared in Examples 1-2 and Comparative Examples 1-3 of this invention; wherein, Figure 2 Image (a) is the SEM image of Example 1. Figure 2 Image (b) is the SEM image of Example 2. Figure 2 (c) in the figure is the SEM image of Comparative Example 1. Figure 2 In the diagram, (d) is the SEM image of Comparative Example 2. Figure 2 (e) in the figure is the SEM image of Comparative Example 3; Figure 3 These are EIS images of garnet-type electrolyte ceramics modified with different amounts of g-C3N4 grain boundaries obtained in Examples 1-2 and Comparative Examples 1-3 of this invention, and a comparison chart of lithium-ion conductivity; wherein, Figure 3 (a) is the EIS diagram of Example 1. Figure 3 (b) is the EIS diagram of Example 2. Figure 3 (c) in the figure is the EIS plot of Comparative Example 1. Figure 3 (d) in the figure is the EIS plot of Comparative Example 2. Figure 3 (e) in the figure is the EIS plot of Comparative Example 3. Figure 3 (f) in the figure is a comparison of the lithium-ion conductivity of all samples; Figure 4 These are comparative graphs showing the impedance changes and lithium-ion conductivity changes of the garnet-type electrolyte ceramics prepared in Examples 1-2 and Comparative Examples 1-3 of this invention after being exposed to air for 30 days; wherein, Figure 4 (a) in the figure is a comparison graph of impedance changes in Example 1. Figure 4 (b) in the figure is a comparison graph of impedance changes in Example 2. Figure 4 (c) in the figure is a comparison graph of impedance changes in Comparative Example 1. Figure 4 (d) in the figure is a comparison graph of impedance changes in Comparative Example 2. Figure 4 (e) in the figure is a comparison graph of impedance changes in Comparative Example 3. Figure 4 (f) in the figure shows the change in lithium-ion conductivity for all samples; Figure 5 This is a constant current charge-discharge diagram of the garnet-type electrolyte ceramic prepared by g-C3N4 grain boundary modification and applied to a lithium-ion solid-state battery, as shown in Example 3 of this invention. Detailed Implementation

[0030] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention. Furthermore, it should be understood that after reading the contents of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims and are all within the protection scope of the present invention.

[0031] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The term "embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment, nor does it specifically limit its independence or connection with other embodiments. In principle, in this application, as long as there are no technical contradictions or conflicts, the technical features mentioned in each embodiment can be combined in any way to form corresponding implementable technical solutions.

[0032] Unless otherwise defined, the technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the use of related terms herein is merely for the purpose of describing particular embodiments and is not intended to limit this application.

[0033] In this invention, unless otherwise specified, all other test materials and instruments are conventional test materials in the field and can be purchased through commercial channels.

[0034] Example 1 This embodiment provides a g-C3N4 grain boundary modified garnet-type electrolyte ceramic with the chemical formula Li. 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -3wt%-g-C3N4.

[0035] Its preparation method includes the following steps: S1, according to Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 The stoichiometric ratios of each element were as follows: 2.21 g of lithium carbonate, 3.94 g of lanthanum oxide, 1.48 g of zirconium oxide, and 0.88 g of tantalum oxide were weighed and mixed to obtain a mixture. The mixture was placed on a planetary ball mill, and 75 g of zirconium oxide balls and 20 mL of isopropanol were added. The mixture was ball-milled at 400 r / min for 12 h to obtain a grinding slurry. The grinding slurry was placed in an oven and dried at 80 °C for 8 h to obtain the precursor powder.

[0036] S2. Place the white melamine powder into a covered alumina crucible, heat it to 550°C in a muffle furnace at a heating rate of 5°C / min, hold it at that temperature for 3 hours, and then cool it to below 50°C in the furnace at a rate of 2°C / min to obtain yellow g-C3N4 powder.

[0037] S3. Place the precursor powder into a covered magnesium oxide crucible and heat it to 1000℃ in a muffle furnace at a heating rate of 5℃ / min, hold it at that temperature for 6 hours, and then cool it to below 50℃ in the furnace at a rate of 2℃ / min to obtain electrolyte powder. Take the electrolyte powder and g-C3N4 powder with a weight of 3wt% electrolyte powder as ceramic mixture. Pour the ceramic mixture into a planetary ball mill, add 20mL isopropanol and 34g zirconia balls, and ball mill at a speed of 400r / min for 12 hours to obtain grinding slurry. Place the grinding slurry in an oven and dry it at 80℃ for 8 hours to obtain electrolyte powder. Weigh 500mg of electrolyte powder, pour it into a mold with an inner diameter of 13mm, and cold isostatically press it at 25℃ and 5MPa for 3 minutes to obtain electrolyte green body.

[0038] S4. Place the electrolyte blank obtained in S3 into a covered magnesium oxide crucible with electrolyte powder (obtained in S3) spread at the bottom, and then cover the surface of the electrolyte blank with electrolyte powder. In a tube furnace under a nitrogen atmosphere, heat to 1150℃ at a heating rate of 5℃ / min and hold for 6h for final sintering. Then cool down to below 50℃ in the furnace at a cooling rate of 2℃ / min to obtain g-C3N4 grain boundary modified garnet type electrolyte ceramic.

[0039] The ionic conductivity of the g-C3N4 grain boundary modified garnet-type electrolyte ceramic in this embodiment is 7.21 × 10⁻⁶. -4 S / cm.

[0040] Example 2 This embodiment provides a g-C3N4 grain boundary modified garnet-type electrolyte ceramic with the chemical formula Li. 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -2wt%-g-C3N4.

[0041] The above Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 The preparation method of -2wt%-g-C3N4 is as follows: S1, according to Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12The stoichiometric ratios of each element were as follows: 2.21 g of lithium carbonate, 3.94 g of lanthanum oxide, 1.48 g of zirconium oxide, and 0.88 g of tantalum oxide were weighed and mixed to obtain a mixture. The mixture was placed on a planetary ball mill, and 75 g of zirconium oxide balls and 20 mL of isopropanol were added. The mixture was ball-milled at 400 r / min for 12 h to obtain a grinding slurry. The grinding slurry was placed in an oven and dried at 80 °C for 8 h to obtain the precursor powder.

[0042] S2. Place the white melamine powder into a covered alumina crucible, heat it to 550°C in a muffle furnace at a heating rate of 5°C / min, hold it at that temperature for 3 hours, and then cool it to below 50°C in the furnace at a rate of 2°C / min to obtain yellow g-C3N4 powder.

[0043] S3. Place the precursor powder into a covered magnesium oxide crucible and heat it to 950°C in a muffle furnace at a heating rate of 5°C / min, hold it at that temperature for 6 hours, and then cool it to below 50°C in the furnace at a rate of 2°C / min to obtain electrolyte powder. Take the electrolyte powder and g-C3N4 powder with a weight of 2wt% electrolyte powder as ceramic mixture. Pour the ceramic mixture into a planetary ball mill, add 20mL isopropanol and 34g zirconia balls, and ball mill at a speed of 400r / min for 12 hours to obtain grinding slurry. Place the grinding slurry in an oven and dry it at 80°C for 8 hours to obtain electrolyte powder. Weigh 500mg of electrolyte powder, pour it into a mold with an inner diameter of 13mm, and cold isostatically press it at 25°C and 5MPa for 3 minutes to obtain electrolyte preform.

[0044] S4. Place the electrolyte blank obtained in S3 into a covered magnesium oxide crucible with electrolyte powder (obtained in S3) spread at the bottom, and then cover the surface of the electrolyte blank with electrolyte powder. In a tube furnace under an argon atmosphere, heat to 1180℃ at a heating rate of 5℃ / min and hold for 5h for final sintering. Then cool down to below 50℃ in the furnace at a cooling rate of 2℃ / min to obtain g-C3N4 grain boundary modified garnet type electrolyte ceramic.

[0045] The ionic conductivity of the g-C3N4 grain boundary modified garnet-type electrolyte ceramic in this embodiment is 7.08 × 10⁻⁶. -4 S / cm.

[0046] Example 3 This embodiment provides a g-C3N4 grain boundary modified garnet-type electrolyte ceramic with the chemical formula Li. 6.5 La3Zr 1.5 (Ta 0.5 )O 12-3wt%-g-C3N4, its preparation method is basically the same as that in Example 1, the only difference is that in S3, 1100mg of electrolyte powder is weighed and poured into a mold with an inner diameter of 18mm for cold isostatic pressing.

[0047] The ionic conductivity of the g-C3N4 grain boundary modified garnet-type electrolyte ceramic in this embodiment is 7.21 × 10⁻⁶. -4 S / cm.

[0048] Comparative Example 1 This embodiment provides a garnet-type electrolyte ceramic prepared without g-C3N4 grain boundary modification, with the chemical formula Li. 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -0wt%-g-C3N4.

[0049] The above Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 The preparation method of -0wt%-g-C3N4 is as follows: S1, according to Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 The stoichiometric ratios of each element were as follows: 2.21 g of lithium carbonate, 3.94 g of lanthanum oxide, 1.48 g of zirconium oxide, and 0.88 g of tantalum oxide were weighed and mixed to obtain a mixture. The mixture was placed on a planetary ball mill, and 75 g of zirconium oxide balls and 20 mL of isopropanol were added. The mixture was ball-milled at 400 r / min for 12 h to obtain a grinding slurry. The grinding slurry was placed in an oven and dried at 80 °C for 8 h to obtain the precursor powder.

[0050] S2. Place the precursor powder into a covered magnesium oxide crucible and heat it to 1000℃ in a muffle furnace at a heating rate of 5℃ / min, hold it at that temperature for 6 hours, and then cool it to below 50℃ in the furnace at a rate of 2℃ / min to obtain electrolyte powder. Pour the electrolyte powder into a planetary ball mill, add 20mL of isopropanol and 34g of zirconia balls, and ball mill at a speed of 400r / min for 12 hours to obtain a grinding slurry. Place the grinding slurry in an oven and dry it at 80℃ for 8 hours to obtain electrolyte powder. Weigh 500mg of electrolyte powder, pour it into a mold with an inner diameter of 13mm, and cold isostatically press it at 25℃ and 5MPa for 3 minutes to obtain an electrolyte preform.

[0051] S3. Place the electrolyte blank obtained in S2 into a covered magnesium oxide crucible with electrolyte powder (obtained in S2) spread at the bottom, and then cover the surface of the electrolyte blank with electrolyte powder. In a tube furnace under nitrogen atmosphere, heat to 1150℃ at a heating rate of 5℃ / min and hold for 5h for final sintering. Then cool down to below 50℃ in the furnace at a cooling rate of 2℃ / min to obtain garnet-type electrolyte ceramic without grain boundary modification by g-C3N4.

[0052] The ionic conductivity of the garnet-type electrolyte ceramic in this comparative example, which was not modified with g-C3N4 for grain boundaries, was 3.46 × 10⁻⁶. -5 S / cm.

[0053] Comparative Example 2 This comparative example provides a garnet-type electrolyte ceramic prepared by grain boundary modification with 1wt%-g-C3N4, the chemical formula of which is Li. 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -1wt%-g-C3N4.

[0054] The above Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 The preparation method of -1wt%-g-C3N4 is as follows: S1, according to Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 The stoichiometric ratios of each element were as follows: 2.21 g of lithium carbonate, 3.94 g of lanthanum oxide, 1.48 g of zirconium oxide, and 0.88 g of tantalum oxide were weighed and mixed to obtain a mixture. The mixture was placed on a planetary ball mill, and 75 g of zirconium oxide balls and 20 mL of isopropanol were added. The mixture was ball-milled at 400 r / min for 12 h to obtain a grinding slurry. The grinding slurry was placed in an oven and dried at 80 °C for 8 h to obtain the precursor powder.

[0055] S2. Place the white melamine powder into a covered alumina crucible, heat it to 550°C in a muffle furnace at a heating rate of 5°C / min, hold it at that temperature for 3 hours, and then cool it to below 50°C in the furnace at a rate of 2°C / min to obtain yellow g-C3N4 powder.

[0056] S3. Place the precursor powder in a covered magnesium oxide crucible and heat it to 1000℃ in a muffle furnace at a heating rate of 5℃ / min, hold it at that temperature for 6 hours, and then cool it to below 50℃ in the furnace at a rate of 2℃ / min to obtain electrolyte powder. Pour the electrolyte powder and g-C3N4 powder (1 wt% of the electrolyte powder mass) into a planetary ball mill, add 20 mL of isopropanol and 34 g of zirconia balls, and ball mill at 400 r / min for 12 hours to obtain a grinding slurry. Place the grinding slurry in an oven and dry it at 80℃ for 8 hours to obtain electrolyte powder. Weigh 500 mg of electrolyte powder, pour it into a mold with an inner diameter of 13 mm, and cold isostatically press it at 25℃ and 5 MPa for 3 minutes to obtain the electrolyte preform.

[0057] S4. Place the electrolyte blank obtained in S3 into a covered magnesium oxide crucible with electrolyte powder (obtained in S3) spread at the bottom, and then cover the surface of the electrolyte blank with electrolyte powder. In a tube furnace under nitrogen atmosphere, heat to 1150℃ at a heating rate of 5℃ / min and hold for 6h for final sintering. Then cool down to below 50℃ in the furnace at a cooling rate of 2℃ / min to obtain garnet-type electrolyte ceramics prepared by grain boundary modification with 1wt%-g-C3N4.

[0058] The ionic conductivity of the 1 wt% g-C3N4 grain boundary modified garnet solid electrolyte in this comparative example is 1.40 × 10⁻⁶. - 4 S / cm.

[0059] Comparative Example 3 This comparative example provides a garnet-type electrolyte ceramic prepared by grain boundary modification with 5wt%-g-C3N4, with the chemical formula Li. 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -5wt%-g-C3N4.

[0060] The above Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 The preparation method of -5wt%-g-C3N4 is as follows: S1, according to Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12The stoichiometric ratios of each element were as follows: 2.21 g of lithium carbonate, 3.94 g of lanthanum oxide, 1.48 g of zirconium oxide, and 0.88 g of tantalum oxide were weighed and mixed to obtain a mixture. The mixture was placed on a planetary ball mill, and 75 g of zirconium oxide balls and 20 mL of isopropanol were added. The mixture was ball-milled at 400 r / min for 12 h to obtain a grinding slurry. The grinding slurry was placed in an oven and dried at 80 °C for 8 h to obtain the precursor powder.

[0061] S2. Place the white melamine powder into a covered alumina crucible, heat it to 550°C in a muffle furnace at a heating rate of 5°C / min, hold it at that temperature for 3 hours, and then cool it to below 50°C in the furnace at a rate of 2°C / min to obtain yellow g-C3N4 powder.

[0062] S3. Place the precursor powder into a covered magnesium oxide crucible and heat it to 1000℃ in a muffle furnace at a heating rate of 5℃ / min, hold it at that temperature for 6 hours, and then cool it to below 50℃ in the furnace at a rate of 2℃ / min to obtain electrolyte powder. Pour the electrolyte powder and g-C3N4 powder (5wt% of the electrolyte powder mass) into a planetary ball mill, add 20mL of isopropanol and 34g of zirconia balls, and ball mill at 400r / min for 12 hours to obtain a grinding slurry. Place the grinding slurry in an oven and dry it at 80℃ for 8 hours to obtain electrolyte powder. Weigh 500mg of electrolyte powder, pour it into a mold with an inner diameter of 13mm, and cold isostatically press it at 25℃ and 5MPa for 3 minutes to obtain the electrolyte preform.

[0063] S4. Place the electrolyte blank obtained in S3 into a covered magnesium oxide crucible with electrolyte powder (obtained in S3) spread at the bottom, and then cover the surface of the electrolyte blank with electrolyte powder. In a tube furnace under nitrogen atmosphere, heat to 1150℃ at a heating rate of 5℃ / min and hold for 6h for final sintering. Then cool down to below 50℃ in the furnace at a cooling rate of 2℃ / min to obtain garnet-type electrolyte ceramic prepared by grain boundary modification with 5wt%-g-C3N4.

[0064] The ionic conductivity of the 5wt%-g-C3N4 grain boundary modified garnet solid electrolyte in this comparative example is 2.69 × 10⁻⁶. - 5 S / cm.

[0065] Characterization tests: X-ray diffraction analysis was performed on the garnet-type electrolyte ceramics prepared in Examples 1-2 and Comparative Examples 1-3, and the results are as follows: Figure 1 As shown. From Figure 1It can be seen that the garnet-type electrolyte ceramics prepared in Examples 1, 2, 1, 2 and 3 can all generate pure cubic garnet phase, indicating that each element was successfully doped to the corresponding site and that doping can promote the synthesis of cubic garnet-type electrolyte. The absence of characteristic peaks for g-C3N4 is due to the low doping amount.

[0066] SEM observations were performed on the garnet-type electrolyte ceramics prepared in Examples 1-2 and Comparative Examples 1-3, and the results are as follows: Figure 2 As shown. From Figure 2 It can be seen that the garnet-type electrolyte ceramics modified with 3wt%-g-C3N4 and 2wt%-g-C3N4 respectively in Examples 1 and 2 have higher density and tighter grain bonding, indicating that adding an appropriate amount of g-C3N4 to the grain boundaries can promote the sintering of the garnet electrolyte. The garnet-type electrolyte ceramic modified with 1wt%-g-C3N4 in Comparative Example 2 has the second highest density and fewer pores between grains, indicating that adding less g-C3N4 to the grain boundaries has little effect on promoting the sintering of the garnet electrolyte. The garnet-type electrolyte ceramic without g-C3N4 modification in Comparative Example 1 and the garnet-type electrolyte ceramic modified with 5wt%-g-C3N4 in Comparative Example 3 have poor density and more pores between grains, indicating that adding excessive g-C3N4 to the grain boundaries will inhibit the sintering of the garnet-type electrolyte.

[0067] The initial impedance of the garnet-type electrolyte ceramics prepared in Examples 1-2 and Comparative Examples 1-3 was tested, and the results are as follows: Figure 3 As shown. From Figure 3 It can be seen that the garnet-type electrolyte ceramics prepared in Examples 1 and 2 have relatively low impedance and strong lithium-ion transport capability, indicating that adding an appropriate amount of g-C3N4 to the grain boundaries and sintering can promote lithium-ion transport. Compared with the garnet-type electrolyte ceramics prepared in Comparative Example 1 without grain boundary modification using g-C3N4, the garnet-type electrolyte ceramics prepared in Comparative Example 2 with grain boundary modification using 1wt%-g-C3N4 have lower impedance and higher lithium-ion conductivity, indicating that adding 1wt%-g-C3N4 to the grain boundaries and sintering can promote lithium-ion transport. The garnet-type electrolyte ceramics prepared in Comparative Example 3 with grain boundary modification using 5wt%-g-C3N4 have increased impedance and decreased lithium-ion conductivity, indicating that adding excessive g-C3N4 to the grain boundaries and sintering will inhibit lithium-ion transport.

[0068] The garnet-type electrolyte ceramics prepared in Examples 1-2 and Comparative Examples 1-3 were exposed to air for 30 days (relative humidity 40%, temperature at room temperature), and their impedance changes were measured using an electrochemical workstation. The comparison graph with the initial impedance results is shown below. Figure 4 As shown. From Figure 4 It can be seen that the garnet-type electrolyte ceramics prepared in Examples 1 and 2 showed very small impedance changes and strong air stability over 30 days, indicating that adding an appropriate amount of g-C3N4 to the grain boundaries and sintering can enhance the air stability of solid electrolyte ceramics. The garnet-type electrolyte ceramics prepared in Comparative Example 2 with 1wt%-g-C3N4 and the garnet-type electrolyte ceramics prepared in Comparative Example 3 with 5wt%-g-C3N4 after grain boundary modification showed the second-lowest air stability, indicating that adding too little or too much g-C3N4 to the grain boundaries and sintering had a poor effect on improving the air stability of solid electrolyte ceramics.

[0069] Performance testing: The 3wt%-g-C3N4 grain boundary modified garnet solid electrolyte prepared in Example 3 was polished with sandpaper, ultrasonically cleaned in ethanol for 45 seconds, and then dried. A coin cell was assembled using lithium sheets as blocking electrodes in an argon-filled glove box. The cycle performance of the symmetric cell was tested using an integrated testing system, and the results are as follows: Figure 5 As shown. From Figure 5 It can be seen that the lithium-ion solid-state battery prepared in Example 3 has good electrochemical stability, which can be maintained at 0.1 mA / cm². 2 It can cycle stably for more than 1800 hours at the specified current density.

[0070] Therefore, the present invention utilizes the above-mentioned g-C3N4 grain boundary modified garnet electrolyte ceramic and its preparation and application, which can improve the density of garnet solid electrolyte, improve ionic conductivity and air stability, and the prepared g-C3N4 grain boundary modified garnet solid battery can exhibit excellent cycle stability.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. g-C3N4 grain boundary modified garnet-type electrolyte ceramic, characterized in that: g-C3N4 grain boundary modified garnet-type electrolyte ceramic has the chemical formula Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 -2~3wt%-g-C3N4.

2. The g-C3N4 grain boundary modified garnet-type electrolyte ceramic according to claim 1, characterized in that: The ionic conductivity of the g-C3N4 grain boundary modified garnet solid electrolyte is 7.08 × 10⁻⁶. -4 ~7.21×10 -4 S / cm, relative density is 95%~97.9%.

3. The preparation of g-C3N4 grain boundary modified garnet-type electrolyte ceramic according to any one of claims 1-2, characterized in that: Includes the following steps: S1, according to Li 6.5 La3Zr 1.5 (Ta 0.5 )O 12 The stoichiometric ratios of each element in the mixture were measured separately for lithium source, lanthanum source, zirconium source and tantalum source, and mixed to obtain a mixture. The mixture was then ground to obtain precursor powder. S2. Calcining melamine yields g-C3N4; S3. The precursor powder is calcined to obtain electrolyte powder. The electrolyte powder and g-C3N4 are used as ceramic mixture. The ceramic mixture is ball-milled and pressed into shape to obtain electrolyte green body. S4. The electrolyte blank is sintered, kept at a certain temperature and then cooled to obtain g-C3N4 grain boundary modified garnet type electrolyte ceramic.

4. The preparation of g-C3N4 grain boundary modified garnet-type electrolyte ceramic according to claim 3, characterized in that: In S1, the lithium source is one or more of lithium carbonate and lithium hydroxide, the lanthanum source is lanthanum oxide, the zirconium source is one or more of zirconium oxide and zirconium oxynitrate, and the tantalum source is tantalum oxide.

5. The preparation of g-C3N4 grain boundary modified garnet-type electrolyte ceramic according to claim 3, characterized in that: In S1, the grinding process uses wet ball milling at a speed of 400-500 r / min for 8-15 h. The dispersant used in wet ball milling is one of isopropanol, ethanol, or methanol, and the milling beads used are zirconia balls. The mass ratio of the mixture, dispersant, and milling beads is 1:(1-2):(3-10).

6. The preparation of g-C3N4 grain boundary modified garnet-type electrolyte ceramic according to claim 3, characterized in that: In S2, the specific operation of calcination is as follows: under an air atmosphere, white melamine powder is placed in a muffle furnace and heated to the target temperature, then kept at that temperature, and then cooled to the furnace temperature ≤50℃. The heating rate is 3-6℃ / min, the target temperature is 550℃, the holding time is 3-4h, and the cooling rate is 1-3℃ / min.

7. The preparation of g-C3N4 grain boundary modified garnet-type electrolyte ceramic according to claim 3, characterized in that: In S3, the specific operation of calcination is as follows: under an air atmosphere, the precursor powder is placed in a muffle furnace and heated to the target temperature, then held at that temperature, and then cooled to the furnace temperature ≤50℃. The heating rate is 3-6℃ / min, the target temperature is 950-1100℃, the holding time is 4-8h, and the cooling rate is 1-3℃ / min.

8. The preparation of g-C3N4 grain boundary modified garnet-type electrolyte ceramic according to claim 3, characterized in that: In S3, wet ball milling is used, with a rotation speed of 400-500 r / min and a time of 8-15 h; The dispersant used in wet ball milling is one of isopropanol, ethanol, and methanol, and the milling beads are zirconia balls. The mass ratio of ceramic mixture, dispersant, and milling beads is 1:(1-2):(3-10).

9. The preparation of g-C3N4 grain boundary modified garnet-type electrolyte ceramic according to claim 3, characterized in that: In S4, sintering is carried out under a nitrogen or argon atmosphere at a temperature of 1100-1200℃, a heating rate of 3-6℃ / min, and a holding time of 4-8h. Cool to 20-50℃ at a rate of 2-6℃ / min.

10. The application of the g-C3N4 grain boundary modified garnet-type electrolyte ceramic as described in any one of claims 1-2 in the preparation of solid-state batteries.